Pseudomonas fluorescens F113 Can Produce a Second Flagellar Apparatus, Which Is Important for Plant Root Colonization - Barahona, Emma; Navazo, Ana; Garrido-Sanz, Daniel; Muriel, Candela; Martínez-Granero, Francisco; Redondo-Nieto, Miguel; Martín, Marta; Rivilla, Rafael (Frontiers in Microbiology, 2016)
The genomic sequence of Pseudomonas fluorescens F113 has shown the presence of a 41 kb cluster of genes that encode the production of a second flagellar apparatus. Among 2535 pseudomonads strains with sequenced genomes, these genes are only present in the genomes of F113 and other six strains, all but one belonging to the P. fluorescens cluster of species, in the form of a genetic island. The genes are homologous to the flagellar genes of the soil bacterium Azotobacter vinelandii. Regulation of these genes is mediated by the flhDC master operon, instead of the typical regulation in pseudomonads, which is through fleQ. Under laboratory conditions, F113 does not produce this flagellum and the flhDC operon is not expressed. However, ectopic expression of the flhDC operon is enough for its production, resulting in a hypermotile strain. This flagellum is also produced under laboratory conditions by the kinB and algU mutants. Genetic analysis has shown that kinB strongly represses the expression of the flhDC operon. This operon is activated by the Vfr protein probably in a c-AMP dependent way. The strains producing this second flagellum are all hypermotile and present a tuft of polar flagella instead of the single polar flagellum produced by the wild-type strain. Phenotypic variants isolated from the rhizosphere produce this flagellum and mutation of the genes encoding it, results in a defect in competitive colonization, showing its importance for root colonization.